2023
DOI: 10.1126/science.abn9033
|View full text |Cite
|
Sign up to set email alerts
|

Soluble organic molecules in samples of the carbonaceous asteroid (162173) Ryugu

Abstract: The Hayabusa2 spacecraft collected samples from the surface of the carbonaceous near-Earth asteroid (162173) Ryugu and brought them to Earth. The samples were expected to contain organic molecules, which record processes that occurred in the early Solar System. We analyzed organic molecules extracted from the Ryugu surface samples. We identified a variety of molecules containing the atoms CHNOS, formed by methylation, hydration, hydroxylation, and sulfurization reactions. Amino acids, aliphatic amines, carboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
95
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 112 publications
(107 citation statements)
references
References 97 publications
12
95
0
Order By: Relevance
“…Nevertheless, terrestrial surficial reservoirs have D-rich isotopic composition relative to ECs and the Earth's mantle, which points toward an additional contribution of CI-like materials to the Earth's surficial reservoirs (Piani et al 2020). Considering the bulk H-content (Yokoyama et al 2023) and the bulk H-isotopic composition (Naraoka et al 2023) of Ryugu's particles as representative of the uncontaminated signature of CI chondrites, we find a ∼3 wt.% contribution from CI-like material to Earth's surficial reservoir that would account for about 30% of the total mass of water in the oceans. Indeed, the lower H abundance for Ryugu's bulk rock relative to CI chondrites compensates for its lower D/H ratio in the mass balance calculation.…”
Section: Implications For the Origin And Distribution Of Water In The...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, terrestrial surficial reservoirs have D-rich isotopic composition relative to ECs and the Earth's mantle, which points toward an additional contribution of CI-like materials to the Earth's surficial reservoirs (Piani et al 2020). Considering the bulk H-content (Yokoyama et al 2023) and the bulk H-isotopic composition (Naraoka et al 2023) of Ryugu's particles as representative of the uncontaminated signature of CI chondrites, we find a ∼3 wt.% contribution from CI-like material to Earth's surficial reservoir that would account for about 30% of the total mass of water in the oceans. Indeed, the lower H abundance for Ryugu's bulk rock relative to CI chondrites compensates for its lower D/H ratio in the mass balance calculation.…”
Section: Implications For the Origin And Distribution Of Water In The...mentioning
confidence: 99%
“…Hydrogen isotopes ( 1 H and 2 H, also called D for deuterium) show large variations among planetary materials and can thus help us to understand the source and distribution of water and volatile elements in the protoplanetary disk (e.g., Robert & Epstein 1982;Alexander et al 2012;McCubbin & Barnes 2019;Vacher et al 2020;Piani et al 2021). The first reports for Ryugu indicated that its bulk hydrogen isotopic composition δD = 252‰ ± 13‰, expressed in δ notation (‰) relative to the standard mean ocean water ratio D/H SMOW = 155.76 × 10 −6 (Naraoka et al 2023), is higher than most of the values measured so far for bulk CI chondrites: Orgueil δD = +182‰ ± 44‰, Ivuna δD = +232 ± 60‰ and Alais δD = +89‰ ± 63‰ (±2 standard deviations; data compilation in Piani et al 2021). In contrast, the D/H of the insoluble organic matter (IOM) obtained after mineral removal by acid dissolution appears be lower in Ryugu (δD = +306‰ and +440‰ for sites A and C, respectively; Yabuta et al 2023) than in the IOM of CI chondrites (δD ≈ +1000‰; Alexander et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent laboratory studies propose the existence of aminomethanol (NH 2 CH 2 OH) and methanediamine (CH 2 (NH 2 ) 2 )-precursors to amino acids and nucleobases-in star-forming regions (Marks et al 2022;Singh et al 2022). In addition, liquid chromatography with fluorescence detection and time-of-flight mass spectrometry (LC-FD/TOFMS) on asteroid (162173) Ryugu return samples suggest the astrophysical presence of four aliphatic amines: methylamine (CH 3 NH 2 ), ethylamine (C 2 H 5 NH 2 ), isopropylamine ((CH 3 ) 2 CHNH 2 ), and propylamine (C 3 H 7 NH 2 ) (Naraoka et al 2023;Parker et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Ryugu bulk samples mainly consist of millimeter to submillimetersized rugged and smooth particles. A JAXA-led phase of initial analysis started in mid-2021, with six international teams (Nakamura et al 2023;Okazaki et al 2022;Yokoyama et al 2023;Naraoka et al 2023;Noguchi et al 2023;Yabuta et al 2023) providing the first general look at Ryugu.…”
Section: Introductionmentioning
confidence: 99%